The status of the translation profession in the European Union - Pym, Anthony 1956- (Anthem Press, 2013)
Based on thorough and extensive research, this book examines in detail traditional status signals in the translation profession. It provides case studies of eight European and non-European countries, with further chapters on sociological and economic modelling, and goes on to identify a number of policy options and make recommendations on rectifying problem areas